HASIL TUMPANG SARI HUTAN TERHADAP PENDAPATAN PESANGGEM DAN BIDANG DASAR TANAMAN POKOK DI CEPU, BLORA - Akub J Abdurachman; Suwidji Basuki (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
The scarcity of agriculture land and the increasing population around the forest have aucsed pressure on the forest resource. Taungya system approach is aimed at improving the prosperity of the people surrounding the forest through tree planting coupled with crops in two years period.The result of observation on Taungya system in Pasar Sore Forest District Administrations, Cepu, Central Java, revealed that the present income from taungya system contributed about 22 % of total income. Other interesting result showed that soil fertilization by peasant, beside gives positive effect on peasant income, it also causes positive impact on the growth of trees basal areas. Some variables analyzed in this study are taungya income (Y1), the cost of production facility such as fertilizer and insectiside cost (X1) man power (X2), non-taungya income (X3), and basal growth (Y2). The relationship resulted in regression models as follows : Y1 = -32,23 + 14,04X1 + 0,23X2 - 0,04X3 (R2 = 0,83) Y2 = 2.009,45 + 326,09 X1 + 2,98 X2 - 1,29 X3 (R2 = 0,78)